O direito ambiental constitucional brasileiro: perspectiva da análise do discurso ecológica - Brandão, Heloanny de Freitas (2016)
The environment matters and its preservation have been large discussed nowadays fostering a variety of academic researches. In this term paper, a linguistic analysis of the contents of the of the Brazilian Environmental Law is proposed, regarding the art. 225 of Brazilian Constitution and its complementary legislation. From this corpus and its emerging demands it is targeted as a general scope to research the harmony between Brazilian Environmental Law and the values of the Deep Ecology included in the theoretical framework of the Ecological Discourse Analysis – EDA. This area suggests new paradigms to be pursued in which mankind establishes a closer and respectful relation with all living beings, including the comprehension of what makes part of the ecosystem. This new area possesses and suggests a holistic and integrated view of the world. In this direction, it is appealed the Econliguistic strand entitled Ecological Discourse Analysis (EDA) as the theoretical basis, which scope is the speech construction study from an ecological perspective considering a range of environment aspects, such as physical, mental and social ones, and not only the social environment reckoned in other strands. Furthermore, this aspect of analysis proposes linguistic studies based on an ideological and eco-ethic lifestyle, also having the Deep Ecology as one of its inspiration sources, thus making part of the EDA. Taking into account the analysis, it was possible comprehend that laws and principles, which assemble the corpus, reveal an embryonal tendency that follows the Deep Ecology values. Nevertheless, the manner in which laws and principles are written demonstrate a strong subordination of laws environment and environment principles to the capitalist and anthropocentric ideologies with priority over environmental ethics, which can harm the assurance of a balanced environment.